Development of High Density Micro-bubble Generator for Environmental Technology - Hirai, S.; Komura, M.; Saechout, V.; Sugaya, S.; Aoki, S.; Takahashi, T. (Elektronika ir Elektrotechnika, 2009)
Micro-bubble is used in engineering field as well as wide range fields such as agricultural, fishery and medical field. This paper has focused on fluid properties in the area where micro-bubble is generated. Especially, kinetic viscosity ν and boundary tension force coefficient σ are focused on. The effect ofνandσon distribution of diameter of micro-bubble is demonstrated experimentally. Ill. 9, bibl. 4 (in English; summaries in English, Russian and Lithuanian).